Bacillus Penicillin Acelase, A Key Catalyst in the Modern Antibiotic Era: A Literature Review - Purnamasari, Lora (RADINKA JOURNAL OF HEALTH SCIENCE, 2025)
Penicillin acylase from the genus Bacillus plays an irreplaceable role as a key catalyst in the modern antibiotic era. This enzyme essentially facilitates the production of 6-aminopenicillanic acid (6-APA), a vital precursor for various semisynthetic beta-lactam antibiotics that continue to be the mainstay in the fight against bacterial infections. The aim of this study was to review Bacillus Penicillin Acylase: A Key Catalyst in the Modern Antibiotic Era," a literature review. This method is a more rigorous and structured approach than a traditional literature review. The goal is to minimize bias and provide a reliable and comprehensive synthesis of research relevant to a specific research question. The expected findings, based on our previous discussions and general knowledge of the field, are as follows: A literature review on "Bacillus Penicillin Acylase: A Key Catalyst in the Modern Antibiotic Era" would likely yield a comprehensive overview of the enzyme's significance, characteristics, production, and applications. The review would highlight how important Bacillus-derived penicillin acylase is for making 6-aminopenicillanic acid (6-APA). 6-APA is always pointed out as the key building block for creating many types of semisynthetic beta-lactam antibiotics, which are essential for today's antibacterial treatments. Different types of bacteria and even different strains of the same type show differences in their enzymes, such as what substances they work best with (like penicillin G or V), how active they are, the best conditions for them to work (like pH and temperature), how stable they are, and whether they produce the enzyme inside or outside the cell.